2021
DOI: 10.3390/molecules26175306
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Fisetin on α-Glucosidase Activity: Kinetic and Molecular Docking Studies

Abstract: The inhibition of α-glucosidase is a clinical strategy for the treatment of type 2 diabetes mellitus (T2DM), and many natural plant ingredients have been reported to be effective in alleviating hyperglycemia by inhibiting α-glucosidase. In this study, the α-glucosidase inhibitory activity of fisetin extracted from Cotinus coggygria Scop. was evaluated in vitro. The results showed that fisetin exhibited strong inhibitory activity with an IC50 value of 4.099 × 10−4 mM. Enzyme kinetic analysis revealed that fiset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…α-Glucosidase inhibitors (AGIs) are first-line drugs to treat diabetes mellitus (DM), and phenolics from plants are excellent sources of AGIs with high efficiency and low side effect ( 35 ). From Figures 3A,B , all samples had significantly α-glucosidase inhibitory abilities in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…α-Glucosidase inhibitors (AGIs) are first-line drugs to treat diabetes mellitus (DM), and phenolics from plants are excellent sources of AGIs with high efficiency and low side effect ( 35 ). From Figures 3A,B , all samples had significantly α-glucosidase inhibitory abilities in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking analysis was performed to explore the structure-activity relationships of these compounds ( Figure 4 ) and the findings were consistent with the α-glucosidase inhibition test. The method of molecular docking provides new perspective for the study of active substances in food [ 35 , 36 ]. 3′-Methoxy puerarin was the most potent compound, with a docking energy of −7.9 kcal/mol (the same as the positive control acarbose).…”
Section: Resultsmentioning
confidence: 99%
“…Fisetin is a natural dietary flavonoid that mainly exists in various fruits and vegetables, such as apples, grapes, cucumbers, and onions [ 163 ]. Through kinetic and molecular docking studies, it was found that fisetin had a potential inhibitory effect on α-glucosidase, which was verified by in vitro experiments [ 164 , 165 ]. Fisetin also has antioxidant, anti-inflammatory, and lipid metabolism-regulating activities [ 166 , 167 ], which can prevent the development of diabetes cardiomyopathy, diabetic neuropathy, and diabetes encephalopathy [ 168 , 169 , 170 ].…”
Section: Natural Compoundsmentioning
confidence: 91%